THE IMPACT OF THE RUSSIAN-UKRAINIAN CONFLICT ON THE RELATIONS OF THE WESTERN BALKAN COUNTRIES TOWARDS THE RUSSIAN FEDERATION - Anđelić, Mile; Hatidza, Berisa Alil (Political Review, 2026)
The subject of this paper is the analysis of the Russian-Ukrainian conflict, which represents one of the most significant geopolitical events of the contemporary international order, with far-reaching consequences for global and regional relations. Even after more than four years of the conflict, which remains the focus of world attention, it serves as an input for unpacking global geopolitics. As a global problem, it has shaken the foundations of world hegemons, raising the question of the extent to which it shifts the foundations of the Western Balkan countries, whose states remain unfinished projects of the post-Cold War era. The diverse interests of the Western Balkan countries and the differences in their foreign policy approaches deepen political disagreements, thereby affecting their causality and regional stability. This paper defines the extent to which the conflict alters their foreign policy stances toward the Russian Federation, and how it reflects on their economies, political, and security relations.Through a historical-comparative method, the paper examines the degree of traditional ties between the Russian Federation and the Western Balkan countries, as well as their divergence aimed at aligning foreign policy with the policies of the European Union and the wider international community, taking into account their aspirations toward European integration. The aim of this paper is to contribute to the understanding of the impact of the Russian-Ukrainian conflict on the foreign policy relations of the Western Balkan countries toward the Russian Federation, and to provide a better insight into contemporary foreign policy developments within a broader international context.
Keywords: Russian-Ukrainian conflict; Western Balkans; Russian Federation; European Union; foreign policy; geopolitical influence